Superior Labrum Anterior Posterior Clinical Exam Techniques - J. Mattison Pike BS; Suvleen K. Singh BS; W. Ben Kibler MD; Josef K. Eichinger MD (SAGE Publishing, 2022)
Background: Superior labrum anterior posterior (SLAP) lesions are prevalent in athletes and the elderly. Therefore, acquiring accurate diagnoses is beneficial for improvement in return to play for athletes and quality of life. A well-done clinical examination can help detect these lesions leading to an early and accurate diagnosis. Indications: Being able to perform a clinical examination for diagnosing SLAP lesions is an important tool for a doctor to know. Currently, there is not a centralized location with published videos that show how to perform these examinations and describe their attributes. This video helps clinicians quickly ascertain how to perform these examinations and learn about the statistical measures associated with them. Technique Description: The 7 exams shown are as follows: modified dynamic labral shear (DLS) test, speed's test, active compression test (O'Brien test), anterior slide test, crank test, Kim test, and the Jerk test. Results: These tests have a wide variety of statistical measures making different ones useful for specific results such as ruling in or ruling out labral lesions. The tests with the highest sensitivity are the modified dynamic labral shear test (72%) and Kim test (61%-92%). The tests with the highest specificity are the modified dynamic labral shear test (98%), anterior slide test (81%-89%), Kim test (88%-99%), and the Jerk test (94%-99%). All of these have a 95% confidence interval except DLS test. Discussion/Conclusions: Some of these tests are more reliable than others when diagnosing labral lesions. Since the dynamic labral shear test and Kim test have the highest sensitivity, they are the most useful tests at ruling out labral lesions. These tests along with the anterior slide test and the Jerk test are the most useful for ruling in labral lesions due to their high specificity. Even though these tests have been proven to be more reliable than others, it still matters which tests the doctors feel comfortable performing accurately for them to use in the clinical setting.